An investigation of the NO/H2/O2 (Lean-deNOx) reaction on a highly active and selective Pt/La0.5Ce0.5MnO3 catalyst - Costa, Costas; Efstathiou, A. M.; Stathopoulos, V. N.; Belessi, Vassiliki (My University, 2001)
The NO/H2/O2 reaction has been studied under lean-burn conditions in the 100-400°C range over 0.1 wt% Pt supported on La0.5Ce0.5MnO3 (mixed oxide containing LaMnO3, CeO2, and MnO2 phases). For a critical comparison, 0.1 wt% Pt was supported on γ-Al2O3 and tested under the same reaction conditions. The maximum in the NO conversion has been observed at 140°C (74% conversion) for the Pt/La0.5Ce0.5MnO3 and at 125°C (66% conversion) for the Pt/γ3-Al2O3 catalyst using a GHSV of 80, 000 h−1. Addition of 5% H2O in the feed stream influenced the performance of the catalyst in a positive way. In particular, it widened the operating temperature window of the catalyst above 200°C with appreciable NO conversion and had no negative effect on the stability of the catalyst for a 20-h run on reaction stream. Remarkable N2 selectivity values in the 80-90% range have been observed on the Pt/La0.5Ce0.5MnO3 catalyst in the 100-200°C range either in the absence or in the presence of water in the feed stream. This result is reported for the first time for the NO/H2/O2 lean-deNOx reaction at least on Pt-based catalysts. A maximum specific integral reaction rate of 397 μmol of N2/s.g of Pt metal was measured at 140°C during reaction with 0.25% NO/1% H2/5% O2/5% H2O/He gas mixture on the 0.1 wt% Pt/La0.5Ce0.5MnO3 catalyst. This value was found to be higher by 40% than that observed on the 0.1 wt% Pt/γ-Al2O3 catalyst at 125°C, and it is the highest value ever reported in the 100-200°C range. A TOF value of 0.49 s−1 was calculated at 140°C for the Pt/La0.5Ce0.5MnO3 catalyst. Temperature-programmed desorption (TPD) of NO and transient titration experiments of the catalyst surface following reaction have revealed important information concerning several mechanistic steps of the present catalytic system. A hydrogen-assisted NO dissociation step and a nitrogen-assisted mechanism for N2 and N2O formation are proposed to explain all the transient experiments performed in a satisfactory manner.
Keywords: Lean de-NOx; NO reduction; NO TPD; Perovskites